2006
DOI: 10.1289/ehp.8548
|View full text |Cite
|
Sign up to set email alerts
|

Dog Ownership Enhances Symptomatic Responses to Air Pollution in Children with Asthma

Abstract: BackgroundExperimental data suggest that asthma exacerbation by ambient air pollutants is enhanced by exposure to endotoxin and allergens; however, there is little supporting epidemiologic evidence.MethodsWe evaluated whether the association of exposure to air pollution with annual prevalence of chronic cough, phlegm production, or bronchitis was modified by dog and cat ownership (indicators of allergen and endotoxin exposure). The study population consisted of 475 Southern California children with asthma from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…In school-age children with asthma, McConnell and colleagues (48) reported that among children who owned a dog (a potential surrogate of endotoxin exposure) the odds ratio for increased bronchitis symptoms per 4.2 ppb increase in NO 2 exposure was 1.49 (95% CI, 1.14-1.95) compared with an odds ratio of 1.16 (95% CI, 0.84-1.60) among children with no dog in the home. In the current study, the prevalence of persistent wheeze among children exposed to high levels of ECAT but low levels of endotoxin was 18%.…”
Section: Discussionmentioning
confidence: 99%
“…In school-age children with asthma, McConnell and colleagues (48) reported that among children who owned a dog (a potential surrogate of endotoxin exposure) the odds ratio for increased bronchitis symptoms per 4.2 ppb increase in NO 2 exposure was 1.49 (95% CI, 1.14-1.95) compared with an odds ratio of 1.16 (95% CI, 0.84-1.60) among children with no dog in the home. In the current study, the prevalence of persistent wheeze among children exposed to high levels of ECAT but low levels of endotoxin was 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to air pollution, especially to local particulate and the traffic-related air pollution (TRP) mixture near children's homes, has been associated with asthma prevalence, incidence, and exacerbation, and with lung function deficits (1)(2)(3)(4)(5)(6)(7)(8). Genetic and toxicologic studies suggest that these relationships are causal (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Young and co-workers for their comments on our recent article [1]. As we highlighted in our article, there are two recent reports indicating that single-nucleotide polymorphisms in the advanced glycosylation end product-specific receptor (AGER) gene, which encodes the receptor for advanced glycation end-products (RAGE), are associated with changes in measurements of airflow obstruction [2,3]. The findings reported by R.P.…”
Section: From the Authorsmentioning
confidence: 85%
“…In their study, they referred to the article of MCCONNELL et al [2] that showed a significant association between ''bronchitis symptoms'' and particulate matter only in the subset of asthmatic children who owned dogs. However, MCCONNELL et al [2] examined the relationship of both dog and cat ownership with air pollution, and reported that effects were somewhat greater among children who owned both a cat and a dog.…”
Section: From the Authorsmentioning
confidence: 99%
See 1 more Smart Citation